Adapting Systems Engineering to the Development of Regional Jets. (28th October 2015) - de Oliveira, Wellington Martins; Jackson, Scott
Abstract: Regional jet developers, like those for mainline jets, must strive to meet the needs of their customers while complying with rigid regulatory requirements. To meet these goals, developers face demands that require judicious adaptation of selected core systems engineering processes to this domain. These demands result from a more severe life cycle environment compared to mainline jets. This severe environment is seen to have a more far‐reaching impact on the architecture and requirements than one would expect. This adaptation requires the developer to consider the selection of which systems engineering processes are most critical to the successful development of an aircraft, and need more adaptation. This paper pays special attention to increased adaptation of stakeholder requirements and requirements analysis processes and their interaction with architectural design and tailoring with other systems engineering processes. The treatment of stakeholder requirements and requirement analysis needs to be efficient due the complexity and severity of the operational environment and life‐cycle scenarios. This issue results in new technologies that when incorporated in regional jet architectures result in high levels of complexity to deal with high level of performance. The architectural process must be rigorously traceable to the requirements process to deal with the top level requirements. A second area of focus is the discussion of organizational roles and responsibilities on stakeholder requirements and requirements analysis within an aircraft company, whether technical or not, these organizations may understand their role in these processes of capture the customer value on a severe life cycle and flow down to a complex architecture. The paper complements this analysis with the characteristic that regional jet developers apply an enhanced systems engineering process with focus on lean documentation.